Tuberculosis Drug Discovery: A Decade of Hit Assessment for Defined Targets - Oh, Sangmi; Trifonov, Lena; Yadav, Veena D.; Barry, Clifton E.; Boshoff, Helena I. (Frontiers in Cellular and Infection Microbiology, 2021)
More than two decades have elapsed since the publication of the first genome sequence of Mycobacterium tuberculosis (Mtb) which, shortly thereafter, enabled methods to determine gene essentiality in the pathogen. Despite this, target-based approaches have not yielded drugs that have progressed to clinical testing. Whole-cell screening followed by elucidation of mechanism of action has to date been the most fruitful approach to progressing inhibitors into the tuberculosis drug discovery pipeline although target-based approaches are gaining momentum. This review discusses scaffolds that have been identified over the last decade from screens of small molecule libraries against Mtb or defined targets where mechanism of action investigation has defined target-hit couples and structure-activity relationship studies have described the pharmacophore.